Gottfried Leibniz in his world: the making of a Savant (1672-1679) - Borowski, A (2022)
This thesis examines Gottfried Wilhelm Leibniz’s early career in its intellectual and social contexts, arguing that his thought must be understood not as the production of an isolated genius but as fundamentally conditioned by the contingencies of his existence as an aspiring scientist and courtier in Mainz (1670-72), Paris (1672-76, with a trip to London in 1673), and Hanover (1676-79). The analysis consists primarily in examining his and his peers’ correspondence during those years and shedding light on how Leibniz sought to position himself at the intersection of the political and scientific realms in France and Germany, but also how his various political and scientific projects were perceived by his contemporaries. The thesis is divided into two parts focusing on his time in Paris and Hanover respectively.